The influence of motivation on job performance among Cosmopoint staff in peninsular Malaysia / Rosnida Yusoh - Yusoh, Rosnida (2020)
The organization’s success is highly depends on employees’ performance. The employee performance closely related with their level of motivation in order to achieve the organizational goals. Motivational problems among employees can lead to work’s performance issues that will bring to company losses. Cosmopoint College Performance Summary in 2017 recorded 16% drop in overall performance but the management neglected that the performance decline correlates with employee motivational factors. The purpose of this study is to examine the influence of motivation on job performance among Cosmopoint staff in Malaysia. The motivational theories of Herzberg Two Factor and Maslow Theory of Needs used to discuss the impact of motivation on the employees’ performance. The factors of motivation focused on salary enhancement, fringe benefits, promotion, supervision and training used to investigate its influence towards employees’ job performance. The study was carried out by using quantitative method. A total number of 127 respondents of this study were selected from 190 employees by using stratified random sampling technique. The instrument of questionnaire used to collect the data. The data collected were analysed by using descriptive statistic and correlation analysis through IBM SPSS Statistics software version 22 to analyse the relationship between motivation factors and job performance. The results indicated that all independent variables had significant correlation on employee’s job performance. The finding of the Multiple Regression discovered 50.7% variation in job performance is accounted from motivational factors used in this study. Furthermore, the results discovered that the most significant motivational factor that influences job performance was supervision.